Reference Values for Chronotropic Index from 1280 Incremental Cycle Ergometry Tests - Sirichana, Worawan; Neufeld, Eric V; Wang, Xiaoyan; Hu, Scott B; Dolezal, Brett A; Cooper, Christopher B (Medicine and science in sports and exercise, 2020)
Clinical cardiopulmonary exercise testing can determine causes of exercise limitation. The slope of heart rate (fC) versus oxygen uptake (V˙O2), which we call the chronotropic index (CI), can help identify cardiovascular impairment. We aimed to develop a reference equation for CI based on a large number of subjects considered to have normal exercise responses. From a database of 13,728 incremental cycle ergometry exercise tests, we identified 1280 normal tests based on the absence of a clinical diagnosis, normal body mass index, and normal aerobic performance plus absence of cardiovascular disease, medications, or ventilatory limitation. A linear mixed-model approach was used to analyze the relationship between CI and other variables. Subjects were age 18-84 yr, and 693 (54.1%) were men. Mean ± SD CI in men was lower than in women, 41.2 ± 9.3 beats per liter versus 63.4 ± 15.7 L. Age (in years), sex (0, male; 1, female), height (in centimeters), and weight (in kilograms) were significant predictors for CI:CIi = 106.9 + 0.16 × agei + 14.3 × sexi - 0.31 × heighti - 0.24 × weighti. The SE of estimates ranged from 10.6 to 11.2 L (median of 10.7 L). We report a reference equation for CI derived from normal subjects. The CI can be used in conjunction with V˙O2max to interpret maximal cardiopulmonary exercise tests. We consider a high CI to be cardiovascular impairment and a low CI plus low V˙O2max to be chronotropic insufficiency.